2017
DOI: 10.1093/sleep/zsx090
|View full text |Cite
|
Sign up to set email alerts
|

Sleep During Menopausal Transition: A 6-Year Follow-Up

Abstract: Study Objectives: Menopausal transition is associated with increased dissatisfaction with sleep, but the effects on sleep architecture are conflicting. This prospective 6-year follow-up study was designed to evaluate the changes in sleep stages and sleep continuity that occur in women during menopausal transition. Methods: Sixty women (mean age 46.0 years, SD 0.9) participated. All women were premenopausal at baseline, and at the 6-year follow-up, women were in different stages of menopausal transition. Polyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 53 publications
0
28
1
Order By: Relevance
“…In contrast, increasing FSH was associated with an increased proportion of SWS (although not with slow-wave EEG activity), which the authors propose as reflecting an adaptive change to counteract the age-related sleep fragmentation. 45 SWAN data also found a link between the change in FSH over time and more SWS as well as a longer total sleep time, 34 which contrasts with findings correlating hormone changes with subjective sleep quality as described earlier. The relationship between reproductive hormones and sleep appears to differ in the reproductive years and earlier in the menopausal transition: in a cross-sectional study of young premenopausal and early menopausal transition women, all in the follicular phase, we found a correlational relationship between higher FSH levels and more WASO but not with other sleep measures, as assessed with single-night, in- laboratory PSG, 46 suggesting an interaction between hormones of the hypothalamic pituitary ovarian axis and sleep–wake regulatory systems that is apparent even in reproductive-age women.…”
Section: Sleep Difficulties Reported Across the Menopausal Transitionmentioning
confidence: 56%
See 2 more Smart Citations
“…In contrast, increasing FSH was associated with an increased proportion of SWS (although not with slow-wave EEG activity), which the authors propose as reflecting an adaptive change to counteract the age-related sleep fragmentation. 45 SWAN data also found a link between the change in FSH over time and more SWS as well as a longer total sleep time, 34 which contrasts with findings correlating hormone changes with subjective sleep quality as described earlier. The relationship between reproductive hormones and sleep appears to differ in the reproductive years and earlier in the menopausal transition: in a cross-sectional study of young premenopausal and early menopausal transition women, all in the follicular phase, we found a correlational relationship between higher FSH levels and more WASO but not with other sleep measures, as assessed with single-night, in- laboratory PSG, 46 suggesting an interaction between hormones of the hypothalamic pituitary ovarian axis and sleep–wake regulatory systems that is apparent even in reproductive-age women.…”
Section: Sleep Difficulties Reported Across the Menopausal Transitionmentioning
confidence: 56%
“…Also, taken together, results suggest that while not all women experience sleep disruption in association with the menopausal transition, subgroups might be more susceptible, such as those with severe HFs and/or insomnia disorder. Most importantly, PSG studies have been cross-sectional except for one 45 and, therefore, are unable to track the trajectories of change in PSG measures in relation to transitioning menopause. Women may begin to experience menopausal symptoms even in the early 40s, when they are still premenopausal, which could confound cross-sectional comparisons between different stages.…”
Section: Sleep Difficulties Reported Across the Menopausal Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…76,77 In contrast, two longitudinal studies showed improved sleep architecture as women entered perimenopause, with greater TST and SWS compared with their premenopausal state. 78,79 There are many potential mechanisms by which sleep quality is affected during the latter part of a woman's life, and they relate to vasomotor symptoms, hormonal changes, agerelated changes, and increases in comorbid conditions such as depression and SDB.…”
Section: Sleep In the Perimenopausal To Postmenopausal Stagesmentioning
confidence: 99%
“…Higher levels of FSH correlated with more PSGdefined wakefulness in women in the menopausal transition similarly to findings in reproductive-age women (de Zambotti et al 2015). On the other hand, another study reported that increasing FSH over time, reflecting more advancement through the menopausal transition, was associated with an increasing proportion of SWS (although not with slow wave EEG activity) (Lampio et al 2017). In an analysis of PSG changes across the menstrual cycle in women in the menopausal transition who were still cycling, we found that the luteal phase was characterized by more awakenings and arousals and less N3 sleep percentage (de Zambotti et al, 2015).…”
Section: Changes In Sleep Across the Menopausal Transitionmentioning
confidence: 54%